Three new compounds from the roots of Juglans mandshurica Maxim. (June 2017) - Li, Jing; Xu, Ping-Sheng; Zou, Zhen-Xing; Zou, Hui; Long, Hong-Ping; Tan, Lei-Hong; Liu, Rui-Huan; Wang, Yi-Kun; Xu, Kang-Ping; Tan, Gui-Shan
Graphical abstract: Highlights: Three new compounds were isolated from the roots of Juglans mandshurica Maxim. Their structures were determined on the basis of extensive spectroscopic analyses. Compound 1 displayed moderate cytotoxicity with IC50 values of 10.08 ± 0.52 μM and 12.44 ± 1.21 μM, respectively. Abstract: A new biflavone glycoside juglbiflavone A (1 ) along with two new lupane-type triterpenes (2-3 ) were identified from the roots of Juglans mandshurica Maxim. Their structures and absolute configurations were elucidated by extensive spectroscopic methods including 1D/2D NMR, HRESIMS and CD. Compound1 is the first example of biflavone glycoside consisted of a flavanol unit and a flavone unit from this genus, which also exhibited moderate cytotoxic activity against SGC-7901 and A549 cell lines in vitro with IC50 values of 10.08 ± 0.52 μM and 12.44 ± 1.21 μM, respectively.